2023
DOI: 10.1111/psyp.14283
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory and non‐oscillatory brain activity reflects fear expression in an immediate and delayed fear extinction task

Abstract: Fear extinction is pivotal for inhibiting fear responding to former threat‐predictive stimuli. In rodents, short intervals between fear acquisition and extinction impair extinction recall compared to long intervals. This is called Immediate Extinction Deficit (IED). Importantly, human studies of the IED are sparse and its neurophysiological correlates have not been examined in humans. We, therefore, investigated the IED by recording electroencephalography (EEG), skin conductance responses (SCRs), an electrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…Leveraging these computed probabilities, we discarded non‐brain components with a likelihood exceeding 90% of being categorized as muscle, eye, heart, line noise, channel noise, or other sources. This 90% threshold aligns with that utilized in Delorme's “Optimized Pipelines” (Delorme, 2023) and other studies (Bierwirth et al, 2023). The remaining independent components were then back‐projected to complete the signal reconstruction.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…Leveraging these computed probabilities, we discarded non‐brain components with a likelihood exceeding 90% of being categorized as muscle, eye, heart, line noise, channel noise, or other sources. This 90% threshold aligns with that utilized in Delorme's “Optimized Pipelines” (Delorme, 2023) and other studies (Bierwirth et al, 2023). The remaining independent components were then back‐projected to complete the signal reconstruction.…”
Section: Methodssupporting
confidence: 79%
“…Being distanced from the primary sources of eye movement artifacts, these sites offered a more appropriate choice for the current study. Furthermore, to manage artifact rejection, we utilized independent component analysis (ICA, infomax algorithm) (Makeig et al, 1995) (Delorme, 2023) and other studies (Bierwirth et al, 2023). The remaining independent components were then backprojected to complete the signal reconstruction.…”
Section: Eeg Data Preprocessingmentioning
confidence: 99%
“…The emotional modulation of alpha ERD seems to reflect the engagement of the motivational systems when a significant/arousing stimulus is detected. Consistently, a modulation of alpha ERD was also observed in studies that manipulated stimulus significance (arousal) by conditioning neutral stimuli (Bacigalupo & Luck, 2022;Bierwirth et al, 2023), and in anticipation paradigms, in which participants had to anticipate negative events, painful/aversive stimulation or possible threats (Del Percio et al, 2006;Onoda et al, 2007). Several conditioning studies reported greater alpha-band suppression following a conditioned stimulus (CS) that was paired with an aversive (CS+) vs. neutral (CS−) outcome (Bacigalupo & Luck, 2022;Chien et al, 2017;Friedl & Keil, 2020Panitz et al, 2019;Yin et al, 2020).…”
Section: Emotional Processing Of Natural Scenes and Alpha Changesmentioning
confidence: 56%
“…Evidence suggests a relationship between excessive alpha power in the temporal region and fear-related processes, including fear conditioning and fear learning circuits [20,27].…”
Section: Temporal Alpha and Fear Conditioning And Learnigmentioning
confidence: 99%
“…Few studies have reported changes in EEG patterns [32], including increased alpha power, in individuals with PTSD [33] or during fear conditioning tasks [27,33]. These changes may indicate dysregulation of fear-learning circuits.…”
Section: Temporal Alpha and Fear Conditioning And Learnigmentioning
confidence: 99%